Ulama's Debate in the Law of Origin of the Fiqih Muammalah and Contract - Efendi Sugianto (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Transactions carried out by both the party we connect between fellow one human _ with other no will miss from something agreement together so we know with law Muamalah , deal together could cause rights and obligations if second split party do something counter or agreement , contract that is maliyah or ghair maliyah . something activities that will arrange how connection between second party or more will be done agreement , then on the contract that alone there is agreement agreement / contract carried out by those who have or the parties who make deal. Difference the views of scholars also occur in the application of condition as well as pillars of contract law , opinions expert fiqh that is according to The school of Imam Hanafiah in question sighat Contract is something get along contract , while expert scholars fiqh put second split the transacting party is target Contract then Sighat is get along must - have contract realized , related can carry out multiple contracts Then there are scholars who are different opinion . Some scholars guide in do multiple contracts based on the Prophet's command to do muamalah or sell buy in various agreement Among second split party , there is a number of opinion expert other fiqh scholars who allow multiple contracts based on rule the law that states that every transaction muamalah could said to be halal except if there is provision the law prohibits previously